Sexuality in Usada Rukmini Tatwa Lontar in Balinese Society - Ariyani, Luh Putu Sri; Maryati, Tuty; Nengah Bawa Atmadja (Universitas Airlangga, 2023)
This study aims to understand the structure, content, and aspects of sexuality based on patriarchal ideology in Lontar Usada Rukmini Tatwa, considered as a cultural text. Thus, to pursue the aim of this study, critical discourse analysis was applied to analyze the text since this analysis technique could deconstruct, interpret, and read cultural texts. The lontar's contents then were analyzed through the following steps, namely conceptualization, conceptualization results, proof, and objectivation. The results of the analysis showed that the structure of the lontar consists of the opening, introduction, content, and the space and time of writing. The results also revealed that the lontar contains recipes for women's beauty and health, husband's courage, sperm health maintenance, and ways to have children for married couples. The contents of the lontars are legitimized religiously and magically so that people believe more in their efficacy. And, it is also found that the contents of this lontar are dominated by erotic and reproductive sexuality discourses based on patriarchal ideology associated with Hinduism. This is symbolized through the phallus as a medium to control women. In conclusion, Lontar Usada Rukmini Tatwa can not only be referred to as an erotic and reproductive sexuality cultural text, but also an ideological cultural text based on Hinduism.